2017
DOI: 10.1177/0269215517691084
|View full text |Cite
|
Sign up to set email alerts
|

The Ottawa panel clinical practice guidelines for the management of knee osteoarthritis. Part two: strengthening exercise programs

Abstract: There are a variety of choices for strengthening exercise programs with positive recommendations for healthcare professionals and knee osteoarthritis patients. There is a need to develop combined behavioral and muscle-strengthening strategies to improve long-term maintenance of regular strengthening exercise programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
128
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(148 citation statements)
references
References 83 publications
(563 reference statements)
1
128
1
2
Order By: Relevance
“…Exercise therapy for patients with knee OA consists of exercise for lower‐limb muscle strengthening, aerobic capacity, and training of daily activities like walking, stair climbing, and transfers (e.g. rising from a chair, getting into and out of a car) (Brosseau et al, 2017a,b; Fernandes et al, ; Fransen et al, ). Comorbidity may limit the exercise tolerance, depending on the type, number and severity of the comorbid disease(s) (de Rooij et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Exercise therapy for patients with knee OA consists of exercise for lower‐limb muscle strengthening, aerobic capacity, and training of daily activities like walking, stair climbing, and transfers (e.g. rising from a chair, getting into and out of a car) (Brosseau et al, 2017a,b; Fernandes et al, ; Fransen et al, ). Comorbidity may limit the exercise tolerance, depending on the type, number and severity of the comorbid disease(s) (de Rooij et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…[40] The Ottawa Panel Clinical Practice Guidelines for the management of knee OA state that strength exercises cause a significant improvement in pain, function, and QoL parameters. [41] The effects of treatments which include general exercise are usually mid-to-long term. [37] Although there is no consensus on the exercise intensity and frequency parameters in knee OA patients, a recent systematic review reported that a total 24 exercise sessions in a 8-12 week period was very effective in knee OA patients, while a once-a-week exercise did not have any effect at all.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of the literature, it was demonstrated that obesity is the risk factor with a major impact on knee osteoarthritis, joint pain and functional impotence (18). Given that obesity has the potential of being reduced, it is possible to propose a physical exercise program and a rigorous diet (19,20). The findings of a recent study on the influence of changes in patellar position in patellofemoral osteoarthritis, using magnetic resonance investigations, conclude that patella alta is a predictive factor for lateral patellofemoral osteoarthritis (21).…”
Section: Discussionmentioning
confidence: 99%